2013 IEEE Biomedical Circuits and Systems Conference (BioCAS) 2013
DOI: 10.1109/biocas.2013.6679651
|View full text |Cite
|
Sign up to set email alerts
|

A 50µm pitch, 1120-channel, 20kHz frame rate microelectrode array for slice recording

Abstract: We present a 1,120 channel active microelectrode array with 50µm pitch recording sites for direct recording of neural slices. Every sensor site has a frontend low noise amplifier and photopixel for correlating optical stimulus with electrical activity. The frontend is AC-coupled and achieves area-efficiency by integrating the large input capacitor and recording electrode directly over the circuitry in conjunction with a single T-capacitor feedback network. Degraded PSRR (63dB) and CMRR (21dB) from the single f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Fixed-wiring arrays include devices without any on-chip circuitry (Alpha MED Science Co., Ltd. 1 ; Multi Channel Systems GmbH 2 ; Thomas et al, 1972 ; Gross et al, 1977 ; Pine, 1980 ; Regehr et al, 1989 ; Nisch et al, 1994 ; Oka et al, 1999 ; Litke et al, 2004 ; Segev et al, 2004 ; Greschner et al, 2014 ), but also MEAs with on-chip circuitry limited to the surrounding of the array (Greve et al, 2007 ) and arrays that include FETs (Offenhäusser et al, 1997 ) and source follower devices directly wired to circuitry outside the array (DeBusschere and Kovacs, 2001 ). Multiplexed arrays employ some sort of multiplexing within the actual array (Eversmann et al, 2003a , 2011 ; Heer et al, 2006 ; Tokuda et al, 2006 ; Aziz et al, 2009 ; Berdondini et al, 2005 , 2009 ; Frey et al, 2010 ; Huys et al, 2012 ; Johnson et al, 2012 , 2013a , b ; Maccione et al, 2013 ; Ballini et al, 2014 ; Bertotti et al, 2014 ).…”
Section: Mea Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Fixed-wiring arrays include devices without any on-chip circuitry (Alpha MED Science Co., Ltd. 1 ; Multi Channel Systems GmbH 2 ; Thomas et al, 1972 ; Gross et al, 1977 ; Pine, 1980 ; Regehr et al, 1989 ; Nisch et al, 1994 ; Oka et al, 1999 ; Litke et al, 2004 ; Segev et al, 2004 ; Greschner et al, 2014 ), but also MEAs with on-chip circuitry limited to the surrounding of the array (Greve et al, 2007 ) and arrays that include FETs (Offenhäusser et al, 1997 ) and source follower devices directly wired to circuitry outside the array (DeBusschere and Kovacs, 2001 ). Multiplexed arrays employ some sort of multiplexing within the actual array (Eversmann et al, 2003a , 2011 ; Heer et al, 2006 ; Tokuda et al, 2006 ; Aziz et al, 2009 ; Berdondini et al, 2005 , 2009 ; Frey et al, 2010 ; Huys et al, 2012 ; Johnson et al, 2012 , 2013a , b ; Maccione et al, 2013 ; Ballini et al, 2014 ; Bertotti et al, 2014 ).…”
Section: Mea Technologymentioning
confidence: 99%
“…The two most prominent preparations investigated with in vitro CMOS MEAs so far are acute retina preparations from mice (Menzler and Zeck, 2011 ; Fiscella et al, 2012 ; Maccione et al, 2014 ), rats (Eickenscheidt et al, 2012 ; Lloyd et al, 2014 ; Stutzki et al, 2014 ), rabbits (Zeck et al, 2011 ; Ballini et al, 2014 ; Fiscella et al, 2014 ), guinea pig (Velychko et al, 2014 ) and humans (Reinhardt and Blickhan, 2014 ); and cultured neuronal cells from snails (Eversmann et al, 2003a ), rats (Hafizovic et al, 2007 ; Heer et al, 2007 ; Gandolfo et al, 2010 ; Lambacher et al, 2010 ; Bakkum et al, 2013 ; Ballini et al, 2014 ) and chicken (Hafizovic et al, 2007 ). Additionally, data from acute slices of the cerebellum (Frey et al, 2009a ; Obien et al, 2014 ), cortex (Ferrea et al, 2012 ; Medrihan et al, 2014 ) and olfactory bulb (Johnson et al, 2013a ) have been shown. Also cultured cardiomyocytes were studied (DeBusschere and Kovacs, 2001 ; Heer et al, 2004 ; Imfeld et al, 2008 ; Sanchez-Bustamante et al, 2008 ; Huys et al, 2012 ) and first results from mice organotypic slices were presented (Gong et al, 2014 ).…”
Section: Mea Technologymentioning
confidence: 99%
“…As a result, neural recording designs have primarily focused on optimizing power efficiency to extend battery life, reduce wireless power harvesting requirements, or minimize heat dissipation [28][29][30][31]. As recording systems scale to higher channel counts (>1000), power-efficient design is further exacerbated by tight area constraints [32][33][34] and high communication data rates [35].…”
Section: Design For Front-end Artifact Immunitymentioning
confidence: 99%
“…(35,36) The feasibility of a megapixel device and the possibility of multimodal imaging are the advantages of a CCD/CMOS-based pH image sensor. Frame rate (fps) 20k fps @28 × 40 pixels (7) 55 fps @20 × 20 pixels (9) 1200 fps @64 × 64 pixels (25) 58 fps @128 × 128 pixels (29) Fig. 1.…”
Section: Ccd/cmos-based Ph Imaging Sensormentioning
confidence: 99%